Selecting Nomination Committee Members—Stakeholders’ Perspective - Hildur Magnusdottir; Audur Arna Arnardottir; Throstur Olaf Sigurjonsson (Sustainability, 2023)
Sustainability is a critical issue for businesses today, and corporate boards and nomination committees play a vital role in promoting sustainable practices within organizations. Nomination Committees (NCs) have become important mechanisms for what has been coined as good or sustainable governance. Stakeholders, however, have different opinions on the merits of these committees. Amongst other things, there is disagreement about whom to select for NCs and the criteria for selection. The composition of NCs can influence board nominations and determine whether the necessary knowledge and skills reside within a board to deal with sustainability and good corporate governance. The aim of this research is to provide insights into stakeholders’ perspectives on what matters when profiling nomination committees’ members. The literature on NCs is underdeveloped, and this research importantly addresses the issue by interviewing 13 individuals who are either shareholders, board members of listed companies, or members of NCs. Additionally, a questionnaire was sent to shareholders, board members, and NC members of the 300 largest companies in Iceland. A total of 138 responses were received. The results show that stakeholders believe it is important to decide upon an NC’s composition prior to electing its members. NC members should have either management or board membership experience. Diversity within the committees is also seen to be important, as it can influence diversity and inclusion overall at the board level. These research results provide important insights and understanding for shareholders and boards of directors when composing nomination committees.